Impacts of the hormonal effects of oral contraceptives on women’s periodontal health: A narrative literature review (Research, Society and Development, 2026)
Oral health is an essential component of overall well-being, reflecting the functional and aesthetic balance of the stomatognathic system. Female hormonal changes, such as those associated with the use of oral contraceptives, may influence the inflammatory response and the oral microbiota, thereby impacting periodontal health. Considering the widespread use of these medications, understanding their relationship with periodontal conditions is important. The present study aimed to analyze, through a narrative literature review, the hormonal influence of oral contraceptives on gingival inflammation and periodontal health in women, taking into account the effects of estrogen and progesterone on periodontal tissues. The review was guided by the following research question: “What is the influence of oral contraceptives on gingival inflammatory processes and periodontal health in women?”. The literature search was conducted in the databases PubMed/MEDLINE, PubMed Central, LILACS, ScienceDirect, and Google Scholar, using the descriptors Oral Health, Contraceptives, and Periodontics, combined with the Boolean operators AND and OR. The findings indicate that hormonal changes associated with the use of oral contraceptives may increase the gingival inflammatory response and promote alterations in the oral microbiota, contributing to a greater susceptibility to periodontal changes, particularly in the presence of dental biofilm. It can be concluded that dental monitoring and preventive measures are essential for maintaining periodontal health in women who use these medications.